Analisis Manajemen Perserta Didik dalam Meningkatkan Motivasi Belajar Siswa - Marget Riayanti Nomleni; Naomi Naben; Merci Sio; Hendrikus U Kaba Jawa; Avandri Alexander Berek; Yanti Yunita Erni Sole,M.Pd (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Student motivation to learn remains one of the persistent challenges faced by schools in Indonesia, particularly in regions with structural and cultural constraints such as East Nusa Tenggara (NTT). Student management is considered a strategic instrument that schools can use to foster learning motivation, since it covers the planning, organizing, implementation, and evaluation of all activities related to students from admission until graduation. This study aims to analyze how student management is implemented to enhance student learning motivation in schools across East Nusa Tenggara. The method used is a literature review, in which data were collected from relevant books, journal articles, and prior research accessed and managed through the Mendeley reference manager, then analyzed descriptively to identify patterns and relationships between student management practices and learning motivation. The review indicates that systematic student management practices, including structured planning of student activities, discipline coaching, active supervision, and the development of academic and non-academic potential, consistently contribute to higher levels of both intrinsic and extrinsic student motivation. Conversely, when student management is implemented inconsistently, students tend to receive inadequate guidance and support, which is reflected in low classroom participation, frequent absenteeism, and elevated dropout rates in several areas of East Nusa Tenggara. This study concludes that strengthening student management practices, particularly through active communication between schools and parents and structured coaching programs, is essential for improving student learning motivation in schools throughout the region.